Can long-term care insurance pilots promote urban industrial structure upgrading? Evidence from a quasi-natural experiment using the China Family Panel Studies - Jiyang Li; Liangyu Chen (Frontiers in Public Health, 2026)
Against the backdrop of population aging and rising demand for disability-related care, long-term care insurance (LTCI) not only shares household care risks but may also reshape urban economic structure by expanding formal care services. This study examines whether China’s LTCI pilots promote urban industrial structure upgrading and explores the associated transmission channels. Treating the staggered rollout of China’s LTCI pilots as a quasi-natural experiment, we match the 2014-2020 China Family Panel Studies with city-level macroeconomic data and estimate a multiperiod difference-in-differences model with individual- and city-level controls, individual and year fixed effects, and city-clustered standard errors. We further apply the Callaway-Sant’Anna estimator to account for staggered adoption and heterogeneous treatment effects. The preferred specification yields an LTCI coefficient of 0.1860, equivalent to approximately 11.3% of the sample mean of the industrial structure upgrading index. The Callaway-Sant’Anna overall average treatment effect on the treated is 0.1974, confirming the baseline finding. The effect is stronger in cities with greater government intervention, in eastern China, and in cities with more developed financial systems. Mechanism analysis indicates that LTCI increases household members’ employment probability and improves household financial product allocation. These findings suggest that LTCI can promote health and eldercare services and related modern service industries through formal care expansion, released household labor supply, and improved household capital allocation, indicating that the effects of LTCI extend beyond household welfare and healthcare to urban industrial transformation.